Original : high speed data compression techniques for large scale storage system change to a partially homomorphic database encryption - Phetsouvanh, Silivanxay (2014)
HELib is a new software library that allows the server to perform computations on encrypted data. Current design of HELib is implemented using the Brakerski-Gentry-Vaiguntanathan (BGV) homomorphic encryption schema, thus data is guaranteed to be more secure at the server end. CryptDB is the database management system that provides provable and practical confidentiality in the face of attack for malicious database administrators. However, The CryptDB does not fully support homomorphic operation in encryption data computation. It is a good opportunity to explore the potential to integrate HELib data encryption mechanism on top of CryptDB system to make a fully homomorphic system in database encryption environment.